TEACHING MODAL VERBS THROUGH DISCUSSING AUTHENTIC VIDEO MATERIALS - Kasimova Yulduz Malikovna (EPRA International Journal of Research and Development (IJRD), 2023)
This article is dedicated teaching modal verbs through discussing authentic video materials and focus on the fulfillment of the homework tasks. Particular attention is paid to the improvement of our class organization for helping our students to achieve a communicative competence.